Mempekerjakan Anak Di Bawah Umur Ditinjau Dari Undang-Undang No 13 Tahun 2003 Tentang Ketenagakerjaan - Al-Anami, Umi Ajizah; Harahap, Nurhotia (Jurnal El-Thawalib, 2024)
This research examines how the implementation of child employment and the views of Labor Law Law No. 13 of 2003. The research used is field research with a qualitative approach. Primary data sources in this study were child labourers, Tangkahan company owners, and community leaders, while secondary data in this study were from books, scientific journals and through references available in various places considered relevant to this research. Data collection techniques with observation, interviews and documentation, with qualitative descriptive data analysis technique. The results in this study indicate that the implementation of child labor in Tangkahan, Aek Manis Village, Sibolga Selatan District, is doing the work of lifting buckets filled with fish and separating fish from one place to another, the work carried out by these children is not in accordance with the rules for child and not in accordance with the view of labor law Law No. 13 of 2003 Article 69 Paragraph 1 which reads "The provisions referred to in Article 68 can be exempted for children aged between 13 years to 15 years to do light work as long as it does not interfere with physical development and health , mental and social”. Then the factors that cause children to work are poverty and compulsion to encourage parents.